Figurative thought and language in action - Brdar, Mario; Brdar-Szabó, Rita (Figurative thought and language ;, 2022)
"The contents of the volume prove the vitality of cognitive linguistic studies of figuration when combined with new research methodologies, in tandem with other disciplines, and also when applied to an ever broader range of topics. Individual chapters are concerned not only with some fundamental issues of defining and delimiting metaphor and metonymy, with the impact of figuration on grammatical forms, but are also exemplary discussions of how figurative language is processed and understood, as well as studies of practical ramifications of the use of figurative language in various types of discourse (the language of media, politics and healthcare communication). Most of the volume assumes a synchronic perspective, but diachronic coverage of processes is not missing either. In short, the volume demonstrates how rewarding it is to return to the true origins of cognitive linguistics for new inspiration and take a fresh start promising a true cornucopia of future results"--